Control of Constitutionality in Ecuador: Many Things to carry in such a Short Trip - Storini, Claudia (2022)
The control of constitutionality is one of the issues that have generated the greatest debates in the Ecuadorian legal sphere, among other factors, this due to the possible normative conflicts that arise in the Constitution —CRE— itself when determining the coexistence of two systems, the mixed and the concentrated by the secondary regulation Organic Law of Jurisdictional Guarantees and Constitutional Control —LOGJCC—, and the contradictory jurisprudence of the Constitutional Court of Ecuador —CCE—. The main objectives of this paper are to analyse from a critical perspective the evolution of the Ecuadorian constitutional control since the approval of the 2008 Constitution, to determine the existing problems in relation to the mixed control of constitutionality and to reflect the existing chaotic jursprudence. For this purpose, a deductive analytical method has been employed, which begins with the study of the theory of constitutional control, followed by the analysis of the normative discipline, and a static analysis of the jurisprudence issued by the CCE in relation to constitutional control. This analysis concludes by representing the reasons in defense of the implementation of a mixed control of constitutionality and, therefore, of a new regulation more attentive to the guaranteeingsystem promoted by the Constitution of Montecristi.